2017
DOI: 10.21767/2573-5365.100037
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms Underlying TGF-β-mediated Complement Activation in Lung Fibrosis

Abstract: While our previous studies suggest that limiting bleomycin-induced complement activation suppresses TGF-β signaling, the specific hierarchical interactions between TGF-β and complement in lung fibrosis are unclear. Herein, we investigated the mechanisms underlying TGF-β-induced complement activation in the pathogenesis of lung fibrosis. C57-BL6 mice were given intratracheal instillations of adenoviral vectors overexpressing TGF-β (Ad-TGFβ) or the firefly gene-luciferase (Ad-Luc; control). Two weeks later, mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…We hypothesized that increased systemic inflammation is due to the elevated complement C3a and C5a levels, as both C3a and C5a can act as chemokines and were previously reported to promote inflammation in lung and kidneys. (29)(30)(31)(32) To test this hypothesis, we injected knockout mice either with vehicle control or small molecule inhibitors of C3aR or C5aR receptors twice weekly during duration of alcohol feeding.…”
Section: C3ar or C5ar Inhibition Abrogates The Effect Of Prmt1 Knockout On The Inflammation In The Lung And Adipose Tissue Of Alcohol-fedmentioning
confidence: 99%
“…We hypothesized that increased systemic inflammation is due to the elevated complement C3a and C5a levels, as both C3a and C5a can act as chemokines and were previously reported to promote inflammation in lung and kidneys. (29)(30)(31)(32) To test this hypothesis, we injected knockout mice either with vehicle control or small molecule inhibitors of C3aR or C5aR receptors twice weekly during duration of alcohol feeding.…”
Section: C3ar or C5ar Inhibition Abrogates The Effect Of Prmt1 Knockout On The Inflammation In The Lung And Adipose Tissue Of Alcohol-fedmentioning
confidence: 99%
“…Studies have confirmed that locally synthesized C3 appears to have a stronger influence on rejection than circulating C3 ( 11 ). Other reports have demonstrated that the epithelial and vascular tissues at local sites of inflammation could secrete complement components ( 12 ). Despite Xavier and Cui have demonstrated that complement C3 activation and macrophage infiltration may play important roles in the progression of interstitial fibrosis in UUO mice and human hypertensive nephropathy, the specific mechanism of local synthesis in renal interstitium by immune cells has not been thoroughly investigated ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 98%
“…is involved in the pathogenesis of IPF [30,31], and increased expression of IGFBP5 and ITGB1 plays a vital role in the development of IPF [32,33]. Our present results suggested that up-regulated hsa_circ_0004099 might promote the development of IPF by decreasing the expression of miR-4633 or miR-9, and further increasing the expression of IGFBP5 or ITGB1, respectively.…”
Section: Discussionmentioning
confidence: 59%